On the stability of public finance in an age of demographic changes - Klonowska, Alina; Pawełek, Barbara (O stabilności finansów publicznych w dobie zmian demograficznych, 2019)
The aim is to determine whether it is possible to achieve a permanent surplus of the social security funds subsector balance to improve the balance of the general government sector. Hypotheses: it is possible to achieve a permanent surplus of the balance of the social security funds subsector in certain macroeconomic conditions; current systemic solutions do not affect the lasting improvement of the balance of social security funds subsector. Model: A linear congruent dynamic model. Results: The balance of the social security funds subsector may be positive and its impact on public finance, favourable. This balance determines the scope and type of system solutions used, but also discretionary decisions. However, the balance changes are not permanent
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 22-33
Keywords: public finance; social security funds; demography; finanse publiczne; fundusze zabezpieczenia społecznego; demografia